Multiple myeloma: A review of the epidemiologic literature - Alexander, Dominik D.; Mink, Pamela J.; Adami, Hans‐Olov; Cole, Philip; Mandel, Jack S.; Oken, Martin M.; Trichopoulos, Dimitrios (International journal of cancer, 2007)
Multiple myeloma, a neoplasm of plasma cells, accounts for ∼∼15% of lymphatohematopoietic cancers (LHC) and 2% of all cancers in the US. Incidence rates increase with age, particularly after age 40, and are higher in men, particularly African American men. The etiology is unknown with no established lifestyle, occupational or environmental risk factors. Although several factors have been implicated as potentially etiologic, findings are inconsistent. We reviewed epidemiologic studies that evaluated lifestyle, dietary, occupational and environmental factors; immune function, family history and genetic factors; and the hypothesized precursor, monoclonal gammopathies of undetermined significance (MGUS). Because multiple myeloma is an uncommon disease, etiologic assessments can be difficult because of small numbers of cases in occupational cohort studies, and few subjects reporting exposure to specific agents in case–control studies. Elevated risks have been reported consistently among persons with a positive family history of LHC. A few studies have reported a relationship between obesity and multiple myeloma, and this may be a promising area of research. Factors underlying higher incidence rates of multiple myeloma in African Americans are not understood. The progression from MGUS to multiple myeloma has been reported in several studies; however, there are no established risk factors for MGUS. To improve our understanding of the causes of multiple myeloma, future research efforts should seek the causes of MGUS. More research is also needed on the genetic factors of multiple myeloma, given the strong familial clustering of the disease. © 2007 Wiley‐Liss, Inc.